2013
DOI: 10.1002/jmri.24329
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal MRI at 3.0 T: LAVA‐flex compared with conventional fat suppression T1‐weighted images

Abstract: The LAVA-Flex sequence offers superior and more homogenous fat suppression of the abdomen than does the FSPGR sequence. The fat-only phase can be a simple and effective method of assessing fatty liver.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 37 publications
1
32
0
Order By: Relevance
“…Therefore, measurement of fat using the "fatonly" image can be measured quantitatively with more accuracy than several other MR adipose tissue imaging methods previously introduced. Moreover, in addition to the information of the amount of body adipose tissue, abnormal conditions of the internal organs can be determined through the contrast of a variety of soft tissues [47,54]. Even in a subject of this study, intra-hepatic abnormal lesion was found in the "water-only" image, which led to a definite diagnosis through additional medical interventions (Fig.…”
Section: Discussionmentioning
confidence: 79%
“…Therefore, measurement of fat using the "fatonly" image can be measured quantitatively with more accuracy than several other MR adipose tissue imaging methods previously introduced. Moreover, in addition to the information of the amount of body adipose tissue, abnormal conditions of the internal organs can be determined through the contrast of a variety of soft tissues [47,54]. Even in a subject of this study, intra-hepatic abnormal lesion was found in the "water-only" image, which led to a definite diagnosis through additional medical interventions (Fig.…”
Section: Discussionmentioning
confidence: 79%
“…The contrast between muscle and fat and between the liver and pathologic lesions were significantly better in the LAVA-Flex sequence than that in FSPGR. This study also revealed that the LAVA-Flex sequence offers superior and more homogenous fat suppression in the abdomen compared to the FSPGR sequence [14].…”
Section: Introductionmentioning
confidence: 92%
“…1 [3,14]. First, circular (21.3 ± 16.1 mm 2 ) ROIs were placed in the superficial fat at eight locations (up, down, left, right, up left, up right, down left, and down right).…”
Section: Data Processingmentioning
confidence: 99%
See 2 more Smart Citations